Exploring foraging decisions in a social primate using discrete-choice models. - Marshall, H; Carter, A; Coulson, T; Rowcliffe, J; Cowlishaw, G (2012)
There is a growing appreciation of the multiple social and nonsocial factors influencing the foraging behavior of social animals but little understanding of how these factors depend on habitat characteristics or individual traits. This partly reflects the difficulties inherent in using conventional statistical techniques to analyze multifactor, multicontext foraging decisions. Discrete-choice models provide a way to do so, and we demonstrate this by using them to investigate patch preference in a wild population of social foragers (chacma baboons Papio ursinus). Data were collected from 29 adults across two social groups, encompassing 683 foraging decisions over a 6-month period and the results interpreted using an information-theoretic approach. Baboon foraging decisions were influenced by multiple nonsocial and social factors and were often contingent on the characteristics of the habitat or individual. Differences in decision making between habitats were consistent with changes in interference-competition costs but not with changes in social-foraging benefits. Individual differences in decision making were suggestive of a trade-off between dominance rank and social capital. Our findings emphasize that taking a multifactor, multicontext approach is important to fully understand animal decision making. We also demonstrate how discrete-choice models can be used to achieve this.